Microfluidic Bioprinting of Heterogeneous 3D Tissue Constructs Using Low-Viscosity Bioink - Colosi, Cristina (Advanced materials (Deerfield Beach, Fla.), 2016)
© 2015 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.